Manajemen Proyek Migrasi Website Company Profile Menggunakan Metode Waterfall pada PT. XYZ - Abiyyu, Hasnan; Rahmada, Davin; Fadha, Mahir; Muhammad Andik Izzuddin (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
This study aims to analyze the application of project management in the migration process of the company profile website at XYZ Company using the Waterfall method. The issues with the previous website were that it still used the WordPress CMS with a static website structure, resulting in content management that was inflexible, difficult to develop, and not user-friendly. The study employed a qualitative method using a case study approach. Data collection was conducted through observation, interviews, documentation, and analysis of the company’s old website. System development was carried out using the Software Development Life Cycle (SDLC) method with the Waterfall model, which includes requirements analysis, system design, system implementation, system testing, and maintenance. The website was developed using React.js for the frontend and CodeIgniter 4 for the backend, implementing the concepts of a Single Page Application (SPA) and a WYSIWYG-based Content Management System (CMS). System testing was conducted using the Blackbox Testing method to ensure all features functioned according to the system’s functional requirements. The research results show that the website migration process successfully addressed the limitations of the previous system and produced a more dynamic, responsive, and easily manageable website. Additionally, the implementation of a fully custom CMS makes it easier for administrators to manage website content more effectively and flexibly. The application of the Waterfall method also helped the website development process proceed in a structured manner in accordance with the predetermined project targets.